2021
DOI: 10.1093/cercor/bhab329
|View full text |Cite
|
Sign up to set email alerts
|

EEG Spatiotemporal Patterns Underlying Self-other Voice Discrimination

Abstract: There is growing evidence showing that the representation of the human “self” recruits special systems across different functions and modalities. Compared to self-face and self-body representations, few studies have investigated neural underpinnings specific to self-voice. Moreover, self-voice stimuli in those studies were consistently presented through air and lacking bone conduction, rendering the sound of self-voice stimuli different to the self-voice heard during natural speech. Here, we combined psychophy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 111 publications
3
27
0
Order By: Relevance
“…High task sensitivity also enabled us to observe that the bone-conduction advantage is most advantageous for other-dominant self-other voice morphs (i.e., containing more other-voice features). This was observed in Study 3 in both self-other and self-familiar tasks (left side of psychometric curves on Fig 3), and replicated in a follow-up EEG study with an independent cohort of participants performing the same self-other task with five times more trials 54 . This suggests that, rather than labelling an ambiguous voice as 'self', bone conduction facilitates discarding an ambiguous voice as being 'not self'.…”
Section: Task Sensitivitysupporting
confidence: 65%
See 3 more Smart Citations
“…High task sensitivity also enabled us to observe that the bone-conduction advantage is most advantageous for other-dominant self-other voice morphs (i.e., containing more other-voice features). This was observed in Study 3 in both self-other and self-familiar tasks (left side of psychometric curves on Fig 3), and replicated in a follow-up EEG study with an independent cohort of participants performing the same self-other task with five times more trials 54 . This suggests that, rather than labelling an ambiguous voice as 'self', bone conduction facilitates discarding an ambiguous voice as being 'not self'.…”
Section: Task Sensitivitysupporting
confidence: 65%
“…While previous self-voice tasks have been characterized by ceiling effects, the paradigm proposed here is able to capture inter-subject variability, which allows us to dissect perceptual specificities (e.g., a bias, general sensitivity, or effects specific to self-or other-voice perception) and personalize studies of self-other VD. Most participants in Studies 1 and 3 (as well as in our follow-up EEG study 54 spontaneously reported that they perceived the self-other VD task to be very difficult and showed poor metacognition, that is they misjudged their ability of successfully performing the task. Moreover, in Study 1 we observed large differences in performance across participants.…”
Section: Task Sensitivitymentioning
confidence: 80%
See 2 more Smart Citations
“…Here, we investigated cardiac and respiratory phase dependency of self‐voice perception. We recorded heartbeat and respiration signals of healthy participants performing two self‐related auditory tasks (self‐other voice discrimination; loudness judgment) (Iannotti et al, 2021 ; Orepic et al, 2021 ). We investigated whether self‐voice perception would differ in trials occurring during different phases of respiratory (inspiration, expiration) and heartbeat (systole, diastole) cycles.…”
Section: Introductionmentioning
confidence: 99%